Potential of GLP-1 Analogs in Managing Hyperphagia and Obesity in Prader-Willi Syndrome: A Review of Efficacy and Safety - Grelewicz, Olga; Juśkiewicz, Adam; Servaas, Elwira; Haber, Mateusz; Kula, Paula; Kotula, Alicja; Czachor, Adrianna; Kucy, Natalia (Quality in Sport, 2024)
Introduction: Prader-Willi Syndrome (PWS) is a genetic disorder marked by hyperphagia, obesity, developmental delays, and behavioral challenges. Traditional treatments like dietary control and growth hormone therapy often fail to effectively manage these symptoms. Recently, glucagon-like peptide-1 (GLP-1) analogs have shown potential in treating PWS. This review assesses the efficacy, safety and mechanisms of GLP-1 analogs in PWS treatment. They improve glycemic control, cardiovascular health, and appetite regulation, contributing to better weight management and overall health in PWS patients. These analogs enhance insulin secretion, inhibit glucagon release, and slow gastric emptying, helping to reduce postprandial glucose spikes and caloric intake. Results: Several small-scale studies and case reports have shown mixed results regarding the effectiveness of GLP-1 analogs in reducing BMI and hyperphagia in PWS patients. Although the studies demonstrated varied outcomes in terms of BMI reduction, all of them reported improvement in satiety or appetite levels. Conclusions: Overall, GLP-1 analogs hold promise for addressing hyperphagia, obesity, and glycemic control in PWS patients, improving their overall health and quality of life. Continued research and long-term studies are essential to establish these benefits and optimize treatment strategies.